(untitled) (United Journal of Interdisciplinary Studies, 2024)
This study has investigated the influence of bank-specific variables on the financial performance of commercial banks in Nepal, focusing on Return on Assets (ROA). Employing both descriptive and causal research designs, data from five commercial banks - NABIL Bank Limited, NMB Bank Limited, Everest Bank Limited, Himalayan Bank Limited, and Sunrise Bank Limited - were analyzed. Bank size, Cash Reserve Ratio (CRR), Capital Adequacy Ratio (CAR), and Non-Performing Loan Ratio (NPLR) were examined in relation to ROA using secondary data sourced from published annual reports spanning from 2012/13 to 2021/22. The study found the coefficient for bank size showed a positive relationship, although statistically insignificant. Conversely, the coefficient for CAR exhibited a significant negative association with ROA, suggesting that higher capital adequacy is linked to lower ROA. The impact of CRR on ROA was negative but not statistically significant, while the NPLR coefficient suggested a negative relationship with ROA, though marginally statistically significant, indicating a potential adverse effect of non-performing loans on ROA that warrants further investigation. Therefore, Commercial banks should enhance their financial performance by optimizing their capital adequacy ratios, as lower CAR is linked to higher ROA. Additionally, they should implement strategies to minimize non-performing loans due to their negative impact on ROA. Further research should focus on identifying other potential bank-specific variables that may influence financial performance.